Penentuan Lot Sizing Persediaan Bahan Baku Baja Tulangan - Endah Setyo Rini; Aulia Kusumawati; Wyke Kusmasari (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
This development poses a challenge to fulfill it by increasing the ability to provide or produce it. These conditions require companies to try to make their products available according to consumer needs. So the company should impose a system of Safety Stock, and ROP (Re-Order Point) or a message back point to ensure the availability of raw materials and the way of production. But sometimes the company doesn't pay attention to the lot size inventory efficiency issue. As a result, manufacturing companies tend to make large purchases without regard to the costs incurred. The purpose of this study is to identify safety stock, inventory costs, lot size, and reorder point for raw materials to then plan the billet raw material inventory. The data in the company has varying characteristics of the demand level so that the data is processed by the Lot Sizing Silver Meal method, the Economic Order Quantity and the Period Order Quantity. From the results of research and analysis, it is known that the safety stock of billet Q275 / 5SP raw materials is 1,046.68 tons and Re-order Points are 11758.04 tons. And from the three optimal lot sizing methods chosen, the Period Order Quantity method with the total cost of ordering raw materials per year is IDR 340,800.00 as much as four orders. Then inventory planning is carried out which results in a complete inventory cost of Rp 2,815,219,200 or resulting in cost efficiency of 17% compared to company policy which is Rp 3,407,764,327